High titre Hog Cholera virus production on Cytodex 3 microcarrier cultures. - Ann Brigitte Cay; De Smet, A; Dubois, N; F. Koenen (Arch Virol, 1989)
In an attempt to produce Hog Cholera virus (HCV) preparations of high titre, optimal growth and trypsinization conditions of PK-15 microcarrier cell cultures were defined. Infecting a PK-15 Cytodex 3 microcarrier culture with HCV increased the yield of virus more than 10 times compared with conventional monolayer culture in Roux flasks.
Keywords: Animals; Cells, Cultured; Classical swine fever virus; Dextrans; Virus Cultivation